FRI0528 Using a validated algorithm to evaluate the effectiveness and cost per effectively treated patient for biologics for rheumatoid arthritis (RA) in patients with employer provided health insurance. (23rd January 2014) - Curtis, J. R.; Schabert, V. F.; Yeaw, J.; Korn, J. R.; Quach, C.; Harrison, D. J.; Yun, H.; Joseph, G. J.; Collier, D. H.
Abstract : Background: Administrative claims contain detailed medication, diagnosis, and procedure data, but their lack of clinical outcomes for RA has limited their use in comparative effectiveness research. A validated claims-based algorithm uses a combination of adherence, dosing, and treatment modifications to estimate biologics' clinical effectiveness as proxies for low disease or remission for RA. 1 In the validation study, "effectiveness" was defined as reaching DAS 28 low disease activity or remission one year after initiating treatment. Objectives: To implement this algorithm in a US managed-care database and calculate the cost per effectively treated patient among biologics approved for moderate to severe RA (etanercept, adalimumab, infliximab, golimumab, and abatacept). Methods: Data were obtained from the commercially insured cohort in the Truven Marketscan Database. The cohort included patients with RA aged 18-63, initiating treatment between January 2007 and December 2010, without biologics 6 months before their first (index) treatment in the database, and continuously enrolled 6 months before and 12 months after their index biologic. Other disease indications for TNF therapy were excluded. The algorithm defines lack of effectiveness as: medication possession ratio < 80% (or fewer infusions/injections than specified on US label), increase in biologic dose or frequency interval, switching biologics, adding new non-biologic Disease Modifying Anti-Rheumatic Drugs, glucocorticoid, dose increase or initiation, or more than one parenteral or intra-articular glucocorticoid injection during follow-up. Drug and administration costs were obtained from allowed amounts on claims. Cost per effectively treated patient was calculated as total drug cost for all patients initiating treatment on a given agent divided by the number of patients in whom that agent was classified as "effective" by the algorithm. Results: The cohort included 15, 351 patients, with a mean age of 49.7 (SD 9.5) years and 78.3% were female. Algorithm effectiveness criteria were met in 30% of etanercept (n=6, 374), 30% of adalimumab (n=4, 661), 20% of infliximab (n=2, 765), 27% of abatacept (n=1, 338), and 29% of golimumab (n=213) patients in the first 12 months of treatment. Mean first year cost per "effectively treated patient" was lowest for etanercept ($49, 952), followed by golimumab ($50, 189), adalimumab ($52, 858), abatacept ($71, 866), and infliximab ($104, 333). Conclusions: Algorithm-defined effectiveness was similar for all agents other than infliximab. Cost per "effectively treated patient" was lower for self-injected than infused biologics using a new, validated claims-based algorithm. References: Curtis JR. et al. Derivation and preliminary validation of an administrative claims-based algorithm for the effectiveness of medications for rheumatoid arthritis. Arthritis Res Ther. 13:R155, 2011 Acknowledgements: Research funded by Immunex Corporation, a wholly owned subsidiary of Amgen Inc., and by Wyeth, which was acquired by Pfizer Inc. in October 2009. Disclosure of Interest: J. Curtis Grant/research support from: Roche/Genentech, UCB, Centocor, CORRONA, Amgen, Pfizer BMS, Janssen, AbbVie, V. Schabert: None Declared, J. Yeaw: None Declared, J. Korn: None Declared, C. Quach Consultant for: Amgen, Inc., D. Harrison Shareholder of: Amgen Inc., Employee of: Amgen, Inc., H. Yun: None Declared, G. Joseph Shareholder of: Amgen, Inc., Pfizer Inc., Employee of: Amgen, Inc., D. Collier Shareholder of: Amgen, Inc., Employee of: Amgen, Inc.